The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.3390/met7090366
|View full text |Cite
|
Sign up to set email alerts
|

DFT Modelling of Cu Segregation in Al-Cu Alloys Covered by an Ultrathin Oxide Film and Possible Links with Passivity

Abstract: Abstract:We modelled with Density Functional Theory (DFT) an Al-Cu alloy covered with a passive film, with several Cu concentrations (from the limit of the isolated atom to the monolayer) at the interface with the oxide, as well as Guinier-Preston 1 (GP1) zones. At low (respectively high) concentration, Cu segregates in the first (respectively second) metal layer underneath the passive film. The Cu monolayer is the most stable configuration (−0.37 eV/Cu atom). GP1 zones were modelled, with a three-copper atom … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 41 publications
2
9
0
Order By: Relevance
“…This is assigned to the preferential oxidation of the Al as already discussed. [29] This Cu enrichment of the matrix at the metal/oxide interface has been previously predicted by computational work [40], where the authors concluded that the presence of oxide could favour Cu segregation at the matrix/oxide interface. Thus, the matrix is mainly composed of metallic aluminium, enriched with copper at the metal/oxide interface, and is covered by an aluminium oxide layer.…”
Section: In Depth Chemical Composition Of the Alloy Surface By Tof-sims Analysessupporting
confidence: 70%
“…This is assigned to the preferential oxidation of the Al as already discussed. [29] This Cu enrichment of the matrix at the metal/oxide interface has been previously predicted by computational work [40], where the authors concluded that the presence of oxide could favour Cu segregation at the matrix/oxide interface. Thus, the matrix is mainly composed of metallic aluminium, enriched with copper at the metal/oxide interface, and is covered by an aluminium oxide layer.…”
Section: In Depth Chemical Composition Of the Alloy Surface By Tof-sims Analysessupporting
confidence: 70%
“…The thickness of the film is about 5 Å, which is comparable to the thickness associated with the oxidation-induced potential gradient and in line with the limiting thickness obtained in ultrahigh vacuum (UHV) experiments . A film of comparable thickness, although based on the structure of γ-Al 2 O 3 , was also utilized by one of us in previous studies as a plausible model in the early stages of passivation. …”
Section: Computational Methods and Technical Detailssupporting
confidence: 73%
“…In particular, in the case of Al alloys and/or intermetallic particles (IMPs), several joint experimental and theoretical works have been performed, where theory helps in interpreting the experimental data. [1][2][3][4][5][6][7][8][9] In other works, DFT models are used to represent typical corrosion situations e.g. alloy dissolution.…”
mentioning
confidence: 99%